(untitled) (PANGEEA, 2025)
This paper presents the deficiencies in the execution of the water supply system of Territorial and Administrative Division Alexandru cel Bun, Neamt County deficiencies that led in January 2021 - February 2021 to the impossibility of supplying drinking water to the population. At the same time, the measures taken to ensure the functioning of the system will be presented, as well as the projects and investments made in the short and medium term to restore the system in parameters. In some areas, a rethinking of the pressure management is described, with the help of which a reduction of the losses from the distribution network was managed, as well as the provision of the necessary flow for a certain target group of users. By introducing an integrated partial monitoring system and its interconnection with the SCADA department, it was possible to monitor both the tank level and the network pressure, as well as the operation of the pressure lifting stations.